The effectiveness of high-fidelity simulation on undergraduate nursing students' clinical reasoning-related skills: A systematic review - Alshehri, Fadiyah D.; Jones, Sophie; Harrison, Denise (Nurse education today, 2023)
High-fidelity simulation is used widely in the education of healthcare professionals; however, its effectiveness in teaching undergraduate nursing students clinical reasoning skills is not known. The objective of this systematic review is to synthesise findings from current literature about the effectiveness of high-fidelity simulation on the development of clinical reasoning-related skills in undergraduate nurses. A systematic review of the effectiveness of high-fidelity simulation was conducted, guided by the Joanna Briggs Institute methodology. Studies included were experimental and quasi-experimental study designs published in English between 2014 and 2020 that investigated clinical reasoning-related skills for undergraduate nursing students. Databases searched included Medline, CINAHL, Embase and the Joanna Briggs Institute of Evidence-based Practice database. A total of 1980 studies were identified and 15 studies met the inclusion criteria. Seven studies were randomised controlled trials, and eight studies were quasi-experimental. The 15 included studies reported 19 outcomes, as studies examined one or more outcomes of clinical reasoning-related skills. Statistically significant results favouring the simulation groups were reported in the following outcomes: clinical reasoning skills (three studies of three studies), critical thinking skills (four out of eight studies), problem-solving (two of four studies), decision-making skills (one of two studies), and clinical judgment skills (two of two studies). High-fidelity simulation was reported to be effective alone and in combination with traditional teaching or other simulation types in improving undergraduate nursing students' clinical reasoning-related skills acquisition. Limitations included cost and availability of high-fidelity simulation to large numbers of students, which have implications for practice. Further research is needed to determine the actual effect of high-fidelity simulation compared to other simulation types on undergraduate nursing students' clinical reasoning-related skills.